The impact of sociodemography, diet, and body size on serum retinol in women 16–35 years of age: SANHANES‐1. Issue 1 (10th November 2017) - Parker, Whadi‐ah; Mchiza, Zandile J.; Sewpaul, Ronel; Job, Nophiwe; Chola, Lumbwe; Sithole, Moses; Labadarios, Demetre
Abstract: To determine the current vitamin A status of a nationally representative sample of women aged 16–35 years, compare it with previous national data, and determine the impact of sociodemography, diet, and body size on vitamin A status, we performed secondary analysis of data on South African women who participated in the first South African National Health and Nutrition Examination Survey (SANHANES‐1). Vitamin A status was assessed by serum retinol, and the findings are reported as means and prevalences with corresponding 95% confidence intervals. Overall, the age‐standardized vitamin A deficiency prevalence was 11.7%, a decrease from previous national data, but serum retinol levels remained lower than in other developing countries. Overall, unweighted, multilevel, multivariate logistic regression showed that vitamin A deficiency was influenced by race only (odds ratio (OR) = 1.89, P = 0.031), while weighted multiple logistic regression for 16‐ to 18‐year‐olds showed that vitamin A deficiency was influenced by locality (OR = 9.83, P = 0.005) and household income (intermediate (OR = 0.2, P = 0.022) and upper (OR = 0.25, P = 0.049)). Despite the decreased prevalence, vitamin A deficiency remains a moderate public health problem in the country. Opportunities for targeted interventions have been identified.